CONCEPTUALIZATION OF PHILANTHROPY IN THE CONTEXT OF ANCIENT POLITICAL SYSTEMS: SOCIO-PHILOSOPHICAL ANALYSIS - Hryhorak, Yuriy (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
This article examines the phenomenon of philanthropy in the context of ancient political systems. It analyzes the evolution of forms of governance from monarchy to tyranny with a focus on the mechanisms of social support that existed in antiquity. Special attention is given to the status structure of society, which defined the groups eligible to receive assistance, as well as the motivations that prompted wealthy citizens to engage in public generosity. The role of private initiative, compulsory philanthropy, and state programs is considered as a means of stabilizing social order. The study concludes that philanthropy in the ancient world held ethical, political, and economic significance. It functioned as a tool for legitimizing power, expressing civic virtue, and managing resources within the framework of the polis or empire. At the same time, its application was shaped by a flexible balance between sincerity of intent and political expediency, which ensured the long-term viability of ancient models of charity.